2015
DOI: 10.1038/srep12285
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, Dielectric and Plasmonic Properties of Two-Dimensional Electride Materials X2N (X=Ca, Sr): A First-Principles Study

Abstract: Based on first-principles calculations, we systematically study the electronic, dielectric, and plasmonic properties of two-dimensional (2D) electride materials X2N (X = Ca, Sr). We show that both Ca2N and Sr2N are stable down to monolayer thickness. For thicknesses larger than 1-monolayer (1-ML), there are 2D anionic electron layers confined in the regions between the [X2N]+ layers. These electron layers are strongly trapped and have weak coupling between each other. As a result, for the thickness dependence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 56 publications
5
72
1
Order By: Relevance
“…The calculated in-plane lattice constants and layer thickness of Ca 2 N monolayer are 3.566 and 2.515 Å, respectively. These values are very close to the experimental values of the corresponding bulk structure (3.66 and 2.51 Å) and the other calculation results of the monolayer Ca 2 N (3.562 and 2.516 Å) [21,22,23,24,25,26]. Based on the optimized structure, two sheets of Ca 2 N monolayer were placed to slide against each other along two high symmetrical paths to model the friction process, as shown in Figure 1.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The calculated in-plane lattice constants and layer thickness of Ca 2 N monolayer are 3.566 and 2.515 Å, respectively. These values are very close to the experimental values of the corresponding bulk structure (3.66 and 2.51 Å) and the other calculation results of the monolayer Ca 2 N (3.562 and 2.516 Å) [21,22,23,24,25,26]. Based on the optimized structure, two sheets of Ca 2 N monolayer were placed to slide against each other along two high symmetrical paths to model the friction process, as shown in Figure 1.…”
Section: Resultssupporting
confidence: 90%
“…Recent studies reported a new type of 2D-layered material of dicalcium nitride (Ca 2 N), which has a hexagonal layered structure in the Rtrue3¯m space group with high c/a ratio, where a and c are in-plane and out-of-plane unit cell dimensions, respectively [21,22,23,24,25,26]. The layered unit (Ca-N-Ca) is closely packed, and adjacent units have a large separation of about 4 Å (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the excess electrons from counting oxidation numbers were confined in the space between the [Ca 2 N] + layers, forming dense twodimensional (2D) electron layer, 6,21 promising for electron dopant, [22][23][24][25][26] batteries, 27,28 and plasmonic device applications. [29][30][31] Meanwhile, monolayer Ca 2 N preserving its unique two-dimensional electron layers in interstitial space was predicted to be stable theoretically and subsequently was grown experimentally. 32,33 This proves the possibility of exfoliation of layered electrides into advanced 2D materials, appealing for applications such as nanoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…A well‐encapsulated intrinsic 2DEG‐FS state based on 2D electride is expected to play an important role in low‐dimensional electronics by realizing nuclear scattering‐free transport. Furthermore, few‐layer 2D electrides, such as Ca 2 N and Sr 2 N, were also suggested to have great potential for plasmonic devices, whose surface‐plasmon‐mode wavelength was found to be significantly shorter than that of conventional noble metal materials …”
Section: Theoretical Designmentioning
confidence: 99%